Exploring Global Research Trends on Smoking and Mental Health: A Bibliometric Analysis - Rinaldi, Martaria Rizky; Hardika, Jelang (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
This bibliometric analysis explores global trends, author productivity, institutional and country contributions, citation patterns, and thematic relationships in the literature linking smoking and mental health. Data from the Scopus database were retrieved using specific keyword combinations related to smoking and mental health, resulting in 1,782 eligible articles after filtering for research quality. The study examines publication trends, identifies high-impact studies, and maps thematic clusters in the field. Results indicate a notable increase in publications after 2000, driven by growing recognition of smoking's impact on mental well-being and the integration of mental health considerations in tobacco control policies. Thematic mapping reveals key areas of focus, including smoking cessation interventions, the neuropsychological effects of nicotine, and socio-economic factors influencing smoking behavior. Despite significant progress, critical gaps remain, particularly in research from low- and middle-income countries, minority populations, and the long-term effectiveness of interventions. This study calls for a more inclusive approach to future research to develop culturally sensitive and accessible interventions, ultimately improving global health outcomes.